Heavy Water Shedding Light on Antigen-Specific T Cell Responses. Issue 3 (March 2018) - Eidsmo, Liv; Gerlach, Carmen
Abstract : CD8 T cells are crucial for long-term immunity. Nevertheless, the in vivo differentiation of human naïve CD8 T cells into effector and memory populations remains ill-defined. A recent study assesses the in vivo turnover of human antigen-specific CD8 T cells and suggests that long-lived memory cells arise from effector cells.